An Empirical Evaluation of Asymmetric Synchronous Collaboration Combining Immersive and Non-Immersive Interfaces Within the Context of Immersive Analytics - Reski, Nico; Alissandrakis, Aris; Kerren, Andreas (Frontiers in Virtual Reality, 2022)
Collaboration is an essential part of data analysis, allowing multiple users to combine their expertise and to debate about the interpretation of data discoveries using their contextual knowledge. The design of collaborative interfaces within the context of Immersive Analytics remains challenging, particularly due to the various user-centered characteristics of immersive technologies. In this article, we present the use case of a system that enables multiple users to synchronously explore the same data in a collaborative scenario that combines immersive and non-immersive interfaces in an asymmetric role setup. Such a setup allows for bridging the gap when applying heterogeneous display and interaction technologies, enabling each analyst to have an independent and different view of the data, while maintaining important collaborative aspects during the joint data exploration. We developed an immersive VR environment (head-mounted display, 3D gestural input) and a non-immersive desktop terminal (monitor, keyboard and mouse) centered around spatio-temporal data exploration. Supported through a real-time communication interface, synchronous collaborative features are integrated in both interfaces, facilitating the users in their ability to establish a shared context and to make spatio-temporal references. We conducted an empirical evaluation with five participant pairs (within-subject design) to investigate aspects of usability, user engagement, and collaboration during a confirmative analysis task. Synthesis of questionnaire results in combination with additional log file analysis, audio activity analysis, and observations, revealed good usability scores, high user engagement, as well as overall close and balanced collaboration of enthusiastic pairs during the task completion independent of their interface type, validating our system approach in general. Further supported through the self-constructed Spatio-Temporal Collaboration Questionnaire, we are able to contribute with discussion and considerations of the presented scenario and the synchronous collaborative features for the design of similar applications.